LEGITYMACJA WSPÓLNOTY MIESZKANIOWEJ W ZAKRESIE DOCHODZENIA ROSZCZEŃ Z TYTUŁU RĘKOJMI ZA WADY FIZYCZNE NIERUCHOMOŚCI WSPÓLNEJ - Trzaskowski, Roman (Wydział Prawa i Administracji UAM, 2005)
The paper deals with issues related to the legitimation of a condominium to claim damages under a warranty for defects in the common property, arising from individual contracts of sale. The main issue discussed is who has the right to claim damages: the individual owners of flats, seeking their rights as arising from general provisions, or the housing community (the condominium as such), on the basis of its rights arising from a joint management of common property. In other words, whether the condominium may claim damages despite the fact that those claims arise from individual contracts of sale. This issue is new in Polish literature, and similar problems are treated and solved differently in different legal systems, especially in the German and Swiss systems. Each of those solutions has certain advantages and disadvantages because the individual’s and group’s interests are always difficult to match and solve. However, the analysis of Polish regulations suggests that the Swiss solution, preferring the individual’s interest, should be adopted. In that solution, legitimation to claim damages under a warranty goes only the individual purchasers, or owners of flats. The housing community (condominium) would be authorised to claim damages only if such claims have been acquired by it by way of a transfer of such rights.
LEGITIMATION OF A HOUSING COMMUNITY (CONDOMINIUM) TO MAKE WARRANTY CLAIMS FOR DEFECTS IN THE COMMON PROPERTY